2012
DOI: 10.3382/ps.2012-02206
|View full text |Cite
|
Sign up to set email alerts
|

The effect of passive immunization against ghrelin on feed and water intake in turkeys

Abstract: Five-week-old turkeys were used to evaluate the effect of passive immunization against ghrelin on feed and water intake and animal behavior. In experiment 1, females were reared using normal feeding and lighting management recommended by the industry. At 5 wk of age (d 0 of experiment 1), birds (n = 40) were individually caged (0.65 × 0.4 × 0.4 m) with free access to feed and water. Feed and water intake were measured 3 times a day (0800, 1200, and 1700 h) by recording the weight of feed or water offered minus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Furthermore, the results reported in this study, as shown in Table 2, are in agreement with those of Lin et al (2011) who reported less food intake in mice with ablation of ghrelin receptor. Nevertheless, the results observed in this study with respect to decreased feed intake in chickens, given in Table 2, contradict those of Vizcarra et al (2012), who studied active immunization of ghrelin in turkeys. Such different research results may be attributed to the differences in the mechanisms of appetite/feed intake regulation (that is, the mechanism of ghrelin immunization differs with GHS-R antagonism) in poultry species (Kaiya et al, 2007 and also different birds strains (Saneyasu et al, 2011).…”
Section: Discussioncontrasting
confidence: 97%
“…Furthermore, the results reported in this study, as shown in Table 2, are in agreement with those of Lin et al (2011) who reported less food intake in mice with ablation of ghrelin receptor. Nevertheless, the results observed in this study with respect to decreased feed intake in chickens, given in Table 2, contradict those of Vizcarra et al (2012), who studied active immunization of ghrelin in turkeys. Such different research results may be attributed to the differences in the mechanisms of appetite/feed intake regulation (that is, the mechanism of ghrelin immunization differs with GHS-R antagonism) in poultry species (Kaiya et al, 2007 and also different birds strains (Saneyasu et al, 2011).…”
Section: Discussioncontrasting
confidence: 97%
“…Similar results were observed when a ghrelin agonist, GHRP-6, was centrally administered in 3-day-old chicks ( Khan et al., 2006 ). In addition, previous studies in our laboratory showed an increase in FI and peck rate in turkeys passively immunized against ghrelin ( Vizcarra et al., 2012 ) as opposed to decreased FI in actively immunized mammals ( Vizcarra et al., 2007 ).…”
Section: Discussionmentioning
confidence: 68%
“…A manual scoring option that integrated pause, rewind and forward choices was used to score start-stop behaviors (sitting and standing) and point events (number of pecks). The videos were watched and analyzed by a human observer as previously described in our laboratory ( Vizcarra et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations